2020
DOI: 10.3390/nu12010219
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Killed Bifidobacterium breve B-3 Enhances Muscle Functions: Possible Involvement of Increases in Muscle Mass and Mitochondrial Biogenesis

Abstract: A previous clinical study on pre-obesity subjects revealed that Bifidobacterium breve B-3 shows anti-obesity effects and possibly increases muscle mass. Here, we investigated the effects of B-3 on muscle function, such as muscle strength and metabolism, and some signaling pathways in skeletal muscle. Male rodents were orally administered live B-3 (B-3L) or heat-killed B-3 (B-3HK) for 4 weeks. We found that administration of B-3 to rats tended to increase muscle mass and affect muscle metabolism, with stronger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
(57 reference statements)
1
26
0
Order By: Relevance
“…The role of Bi dobacteria in muscle function has been well studied recently. An experimental study investigated the effects of Bi dobacterium breve B-3 (B-3) on muscle function on mice [35]. And it turned out that the administration of B-3 on the mouse model could increase muscle mass and affect muscle metabolism, and the grip strength of heat-killed B-3 group was signi cantly higher than that of the control group [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Bi dobacteria in muscle function has been well studied recently. An experimental study investigated the effects of Bi dobacterium breve B-3 (B-3) on muscle function on mice [35]. And it turned out that the administration of B-3 on the mouse model could increase muscle mass and affect muscle metabolism, and the grip strength of heat-killed B-3 group was signi cantly higher than that of the control group [35].…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study investigated the effects of Bi dobacterium breve B-3 (B-3) on muscle function on mice [35]. And it turned out that the administration of B-3 on the mouse model could increase muscle mass and affect muscle metabolism, and the grip strength of heat-killed B-3 group was signi cantly higher than that of the control group [35]. Similarity, another study suggested that dietary supplementation with Bi dobacterium breve BR03 attenuates performance decrements and muscle tension in the days following muscle-damaging exercise [36].…”
Section: Discussionmentioning
confidence: 99%
“…In another clinical study on healthy elderly subjects who were supplemented with a combination probiotic containing B. breve B-3 and assigned to moderate resistance training, the results showed that the combination probiotic containing B. breve B-3 improved mental condition, body weight, and bowel movement frequency [ 85 ]. Administration of both live and heat-killed B. breve B-3 to 8-week-old SD rats increased muscle mass and muscle strength, promoted oxidative muscle fiber composition, and modified metabolic functions, and the effects possibly occurred via the Akt and AMPK pathways [ 38 ]. In these studies, heat-killed B. breve B-3 showed equivalent or even stronger effects compared with live cells.…”
Section: Probiotics For Anti-aging Reported From Research Modelsmentioning
confidence: 99%
“…lactis DSM10140 In vitro Suppression of PI3K/Akt signal pathway over-activation Regulation of Salmonella induced IL-8 response and prevention of Salmonella infection 2016 44 B. animalis subsp. animalis (IM386) In vitro and in vivo Up-regulation of PKC and PI3K/Akt anti-apoptotic pathways Regulation of TJ and actin cytoskeleton, and promotion of general immune tolerance 2021 34 B. breve B-3 In vivo Promotion of AMPK and Akt/mTOR signaling phosphorylation Elevation muscle mass 2020 57 B. breve C50 (BbC50sn) In vitro Induction of PI3K/Akt, p38MAPK, and ERK pathways reduction of allergic and inflammatory disorders 2008 58 L. johnsonii N6.2 In vivo Reduction of mTORC1-activating phosphorylation of pAKT-T308 and pAKT-S473 Reduction of metabolic syndrome disease 2018 59 L. casei In vitro Down-regulation of PI3K/Akt/NF-κB phosphorylation Induction of apoptosis and inhibition of gastric cancer 2013 60 L. casei Zhang (LCZ) In vivo Decreasing inflammatory cytokines, and inhibiting the hyperactivation of PI3K/Akt/NF-κB and p -STAT3 pathways Prevention and treatment of ulcerative colitis 2019 95 L. paracasei subp. paracasei X12 In vitro ...…”
Section: Introductionmentioning
confidence: 99%